Centralized resource allocation with emission resistance in a two-stage production system: Evidence from a Taiwan's container shipping company. (December 2016) - Yu, Ming-Miin; Chen, Li-Hsueh
Graphical abstract: Resource reallocation based on common inputs shared among both processes of each route. Highlights: A centralized network data envelopment analysis model for resource reallocation is proposed. The proposed model considers carbon emission and links it with energy reductions. Inputs are classified into common inputs, specific inputs and energy inputs. Common inputs are not only shared among sub-units but also the production and service processes. Both non-radial and radial variables are incorporated into the proposed model. Abstract: This paper proposes a centralized network data envelopment analysis model that combines the centralized data envelopment analysis model and network data envelopment analysis to allocate resources among sub-units. In the proposed model, this paper also considers the situations in which undesirable outputs are jointly produced with desirable outputs, the reduction of undesirable outputs is associated with the reduction of energy inputs, and some inputs are dedicated to the specific sub-unit while some inputs are shared among sub-units. To comprehensively investigate this issue, two cases are discussed. One case explores the situation in which common inputs are shared among the first process of sub-units, while the other case explores the situation in which common inputs are also shared among two processes of sub-units. The proposed model is illustrated in an empirical example of 14 Asian shipping routes operated by a Taiwanese container shipping company. In order to avoid organizational resistance, minor and major adjustment policies are demonstrated. The minor adjustment policy transfers inputs among routes but maintains the original levels of input resources, whereas the major adjustment policy reduces the total amount of input resources. The results provide valuable information for the centralized decision-maker on how to reallocate resources among the sub-units.